Précis de l'histoire de la musique, depuis les temps les plus réculés - Andries, Jean-Jacques 1798-1872 (Ghent De Busscher frères, 1862)
Jean Jacques Andries (1798-1872)"Ce qui entrave encore ces eludes, c'est la cherte et parfois la rarete les bons ouvrages didactiques, surtout des ouvrages anciens et etrangers, si interessants a consulter. Pour obvier a cela, nous avons compose ce Parus De l'Historie De La Musique, depuis les temps les plus recules et chez tous les peuples du globe."
Andries was a Belgian violinist, musicologist, composer and music teacher. Professor of violin at the Ghent Conservatory from its founding in 1835, he also led a chamber ensemble class, taught harmony and composition, and became director of the conservatory. Among his students is Karel Miry. In 1859 he retired. Author of the opera “The Orphan” (French: L’orpheline), concertina for violin and orchestra and some other musical works. Published the books “Historical overview of all currently used musical instruments” (French Aperçu historique de tous les instruments de musique actuellement en usage; 1856), “ Notes on bells and carillons" (French: Remarques sur les cloches et carillons; 1868), as well as a book on the flute.
Ex libris C.I.C.M. Bibliotheca Scholasticatus S. Josephii Lovanii (stamp)
Ex libris P. Noël Namur (manuscript)
suivi de notices sur un grand nombre d'écrivains didactiques et théoriciens de l'art musical
Keywords: 19th Century (1801-1900); Music history